An Analysis of Battle of Waterloo and Napoleonic era from the perspective of Victor Hugo‟s Les Miserable - Das, Gunjan Jyoti; Das, Gunjan Jyoti (International Journal of Psychosocial Rehabilitation, 2020)
The battle of Waterloo and Napoleon Bonaparte has a special place in the course of world history. The defeat of Napoleon Bonaparte in this battle led to restoration of pre revolutionary administration in France. The united anti-revolutionary group of Europe organized Vienna congress and restored the monarchial system again and made the all possible arrangements to put check on the revolutionary ideas in Europe. Before the further discussion on the consequence of battle of Waterloo, it is important to know the background of the event thoroughly.